Čaščenje Nimf in Fontana v vzhodnoalpskem prostoru - Visočnik, Julijana (Studia Historica Slovenica, 2020)
In July 2004, while trenching for the construction of a gas pipeline in the vicinity of the church in Šentpavel pri Domžalah, archaeologists found an altar devoted to Nymphs and Fontanus. It was discovered north of the former Roman villa rustica, which had been researched in 1997, 1998, and 1999, in the surroundings of the church of St Paul. Judging from the inscription, the altar was originally erected by a water source, while the dedication was supposed to ensure that it never dried up, possibly even to guarantee its healing powers. Since this altar has not yet been published according to the principles of epigraphic methodology, it seems appropriate to properly set it into the context of previously known facts about the worshipping of Nymphs and Fontanus (or Fons) in the Slovenian territory or in the wider Eastern-Alpine area.
Keywords: antika; arheologija; rimski bogovi; Slovenija; Vzhodne Alpe